Reconfiguration algorithms for degradable VLSI arrays with switch faults - Zhu, Yuanbo (2013)
The problem of reconfiguring two-dimensional VLSI arrays with faults is to find a maximum logical array without faults. The existing algorithms only consider faults associated with processing elements, and all switches and links are assumed to be fault-free. But switch faults may often occur in the network-on-chips with high density. In this paper, two novel approaches are proposed to tackle the reconfiguration problem of degradable VLSI arrays with switch faults. The first approach extends the well-known existing algorithm with simple pre-processing and row bypass scheme. The second one employs a novel row and column rerouting scheme to maximize the size of the logical array. Simulation results show that the proposed two approaches can effectively generate the logical arrays on the given host array with switch faults, and the second algorithm performs more favorably with the increasing number of the switch faults.